(untitled) (Journal of School Administration Research and Development, 2016)
This study investigated the relation be- tween the easyCBM Benchmark Assessments in both mathematics and reading and the Smarter Balanced assessment, widely adopted across the United States. Data for the study were obtained from a convenience sample of approximately 1,000 students per grade in grades 3-8 provided by two school districts in the Pa- cific Northwest. Results indicate that the easyCBM CCSS math assessments are a strong predictor of the Smarter Balanced total math score, with correlations ranging from .69 to .84 across grades and seasonal benchmarks. Linear regression analyses indicate that the different easyCBM CCSS math measures account for 68% to 77% of the variance in Smarter Balanced total math score. In addition, all of the easyCBM read- ing assessments are significantly related to the Smart- er Balanced English language arts total score, with correlations ranging from .50 to .69 across grades, measure types, and seasonal benchmarks. Linear re- gression analyses indicate that the different easyCBM reading measures account for 50% to 62% of the vari- ance in Smarter Balanced English language arts score.